Integration of an in vitro renal cellular set of tools with systems biology modelling to predict the renal contribution to the pharmacokinetics of a drug - Taylor, Patrick (2020)
The aim of this study was to develop an in vitro model of the kidney that could facilitate predictions of renal contribution to the pharmacokinetics drugs and to identify potential drug-drug interactions (DDIs). Porcine and murine proximal/distal tubule cells were grown as monolayers on Transwell filter supports. The integrity of these monolayers was assessed using Lucifer yellow permeability, trans-epithelial electrical resistance (TEER) and immunocytochemistry imaging of ZO-1 tight junction proteins. A range of transporters were expressed at the mRNA level including OAT1, OAT3, OCT1, OCT2, MRP2 and MATE2-K. Flow activated cell sorting (FACS) was used to identify the cell membrane proteins CD10 and MUC1 which are markers of proximal and distal tubule cells respectively. Transporter function was assessed using the OAT3 substrate penicillin V and OCT2 substrate metformin. DDI studies utilised probenecid and rifampicin as OAT inhibitors. Cimetidine and amiloride were used as inhibitors for the OCT substrate metformin. Carbamazepine was included as a negative control and to represent non-transporter mediated diffusion across the monolayer. Varying substrate concentration from 0.5 to 20 µM was utilised to detect if the transport processes were saturable. Two, three and four compartment models of the kidney were designed and manipulated to derive equations for renal clearance.